Geochronology and geochemistry of the Fogang granitic batholith and its implications for uranium mineralization - Hu, Peng; Ding, Wei-Cheng; Liu, Bin; Wei, Wen-Fang; Qi, Jia-Ming; Qiu, Liang (Frontiers in Earth Science, 2025)
The E–W-striking Fogang granitic batholith represents the largest composite batholith in Guangdong Province. To date, the only known uranium deposit, the Pajiang deposit, has been identified in the southwestern portion of the Fogang granitic batholith. This deposit is hosted by porphyritic biotite granite (PBG) and two-mica granites. Nevertheless, the age, petrogenesis, and genetic relationships between these lithologies and the associated uranium mineralization remain subjects of ongoing debate. In this study, zircon U–Pb dating, whole-rock geochemistry, and zircon trace-element analyses of porphyritic biotite granite and two-mica granites in the Pajiang area of the Fogang granitic batholith were systematically investigated. The results reveal that the geochronologies of the porphyritic biotite granite, medium-to-fine-grained two-mica granite (M-FG TMG), and fine-grained two-mica granite (FG TMG) are 156.7 ± 0.7 Ma (MSWD = 0.2, n = 11), 155.3 ± 1.6 Ma (MSWD = 0.5, n = 12), and 153.8 ± 1.4 Ma (MSWD = 0.6, n = 24), respectively. The porphyritic biotite granite is characterized by high SiO2, high alkalis, and a metaluminous to peraluminous composition (A/CNK = 0.95–1.21; mean = 1.08) but low rare earth contents (∑REE: 107 ppm–465 ppm, mean = 183 ppm) and negative Eu anomalies (δEu = 0.12–0.60, mean = 0.29), indicative of a highly fractionated S-type granite. The porphyritic biotite granite, medium-to-fine-grained two-mica granite, and fine-grained two-mica granite all show high Rb/Sr values (1.52–41.7, with a mean of 8.76), indicating derivation from mature continental crust material. The porphyritic biotite granite has CaO/Na2O ratios of 0.06–0.70, suggesting that its source was a mixture of pelitic and clastic rocks. The medium-to-fine-grained two-mica granite and fine-grained two-mica granite have lower CaO/Na2O ratios, indicating derivation from predominantly pelitic sources. Zircon trace-element data indicate that the porphyritic biotite granite has a relatively higher oxygen fugacity (fO2 = −13.2), followed by the medium-to-fine-grained two-mica granite and the fine-grained two-mica granite, which exhibit relatively lower oxygen fugacities (fO2 = −20.2 and −17.3, respectively). Under low-oxygen-fugacity conditions, uranium tends to crystallize as independent uranium-bearing minerals or uranium-rich minerals during the magmatic stage; in contrast, under high-oxygen-fugacity conditions, uranium is more likely to be incorporated into refractory accessory minerals (e.g., zircon and monazite). The crystallization processes of the medium-to-fine-grained two-mica granite and the fine-grained two-mica granite are thus particularly favorable for the formation of uranium-bearing minerals such as uraninite and thorite. These minerals are susceptible to dissolution by hydrothermal fluids during subsequent Late Cretaceous uranium mineralization, thereby releasing uranium and providing a substantial source for mineralization. This further suggests that the two-mica granites serve as significant uranium source rocks for granite-type uranium deposits and hold favorable implications for mineral exploration.